Deformation of the Nankai Trough inner accretionary prism: The role of inherited structures. (20th February 2016) - Boston, Brian; Moore, Gregory F.; Jurado, María José; Sone, Hiroki
Abstract: Accretionary prisms commonly grow seaward, with the strata of the inner prism consisting of older, previously accreted outer prism rocks overlain by thick fore‐arc basin strata. We focus on the Nankai Trough inner accretionary prism using three‐dimensional (3‐D) seismic data and logging data from the Integrated Ocean Drilling Program (IODP). We update the 3‐D seismic volume using well velocity data to better constrain deeper horizons. Interpretation of these horizons reveals multiple folds with axial surfaces that strike near parallel to modern outer prism thrust faults, and we interpret that these folds formed as a result of thrust faulting. Reactivation of one inner prism thrust fault continued until at least ∼0.44 Ma, after the modern fore‐arc basin formed, indicating that the inner prism had continued deformation until that time. Structural restorations of these folded seismic horizons demonstrate that ∼580 m of slip occurred on this steeply dipping reactivated thrust after fore‐arc basin formation. Structural interpretation and analysis of logging‐while‐drilling data, including borehole images, in the deep inner prism revealed intense deformation of a generally homogenous lithology characterized by bedding that dips steeply (60°–90°), intersected by faults and fractures that have a range of dips and densities. Our study of the deep Kumano Basin provides new insights into the structure of the inner prism and reveals that although the inner prism has partially preserved inherited outer prism structures, these older folds and faults are steeply rotated and cut by multiple fracture populations during subsequent deformation. Key Points: Inherited structures created at the outer prism are partially preserved within the inner prism A reactivated fault within the inner prism indicates a dynamic history Steeply dipping beds with multiple fracture populations are found at depth